2022
DOI: 10.3390/ijms23158586
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Alpha-, Beta-, and Gamma-Synucleins in Brainstem Regions of a Non-Human Primate Model of Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is characterized by cell loss in the substantia nigra and the presence of alpha-synuclein (α-syn)-containing neuronal Lewy bodies. While α-syn has received major interest in the pathogenesis of PD, the function of beta- and gamma-synucleins (β-syn and γ-syn, respectively) is not really known. Yet, these proteins are members of the same family and also concentrated in neuronal terminals. The current preclinical study investigated the expression levels of α-, β-, and γ-synucleins in brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…Several limitations have to be acknowledged in this study. First, current studies (13,30) have shown the association between vagus nerve and the midbrain dopaminergic neurons. Nevertheless, the correlation between vagus nerve and neuron network in other locations has not been extensively studied and validated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several limitations have to be acknowledged in this study. First, current studies (13,30) have shown the association between vagus nerve and the midbrain dopaminergic neurons. Nevertheless, the correlation between vagus nerve and neuron network in other locations has not been extensively studied and validated.…”
Section: Discussionmentioning
confidence: 99%
“…In PD, the degeneration and loss of dopaminergic neurons in the brain are closely related to the abnormal accumulation of α-synuclein. The increased expression of α-synuclein in the midbrain dopaminergic neurons is positively correlated with the severity of movement disorders in PD ( 30 ). The translocation of dopamine to synaptic vesicles by VMAT2 prevents the formation of neurotoxic derivatives of dopamine in the cytosol ( 31 - 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The overwhelming majority of publications on synucleins are dedicated to α-synuclein due to its involvement in Parkinson’s disease (PD) and other synucleinopathies. Yet, two other proteins β- and γ-synucleins belonging to the same family are localized predominantly in neuronal terminals and implicated in the long-term modulation and preservation of nerve terminal function and dopamine homeostasis [ 7 ]. As a result, they deserve more attention to better understand the functionality of nervous system and role in carcinogenesis.…”
Section: Three Members Of the Synuclein Familymentioning
confidence: 99%
“…Examination of synucleins in a non-human primate model of PD showed that the expression of all three members of the family was increased in the substantia nigra after treatment with prodrug to the neurotoxin-1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). This increase correlates positively with the loss of cells and motor score [ 7 ]. The expression of the three types of synucleins was also increased in the dorsal raphe nucleus, but only α- and γ-synucleins are associated with the loss of cells and cell loss.…”
Section: Three Members Of the Synuclein Familymentioning
confidence: 99%
See 1 more Smart Citation